2021
DOI: 10.1021/acsami.1c00842
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Photo-controlled Permeability of a Biomimetic Polymersome with Sustained Drug Release and Efficient Tumor Therapy

Abstract: Synthetic polymersomes have structure similarity to biovesicles and could disassemble in response to stimuli for "on-demand" release of encapsulated cargos. Though widely applied as a drug delivery carrier, the burst release mode with structure complete destruction is usually taken for most responsive polymersomes, which would shorten the effective drug reaction time and impair the therapeutic effect. Inspired by the cell organelles' communication mode via regulating membrane permeability for transportation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…In an example of simultaneous photoconversion with UCNPs and photocleavage for multiple therapies, He and collaborators developed a nanoreactor based on oligo(ethylene glycol) monomethyl ether methacrylate (OEGMA) mixed with synthetically derived eosin Y (derived EoS) and ONB oxycarbonyl aminoethyl methacrylate (NBOC) hydrophobic monomer with an ONB photolabile group ( Figure 12 ) [ 303 ]. The resulting amphiphilic diblock copolymer P(OEGMA-co-EoS)-b-PNBOC (POPN) was synthesized via RAFT polymerization.…”
Section: Light-responsive Polymersomes For Anticancer Therapeutic Del...mentioning
confidence: 99%
See 1 more Smart Citation
“…In an example of simultaneous photoconversion with UCNPs and photocleavage for multiple therapies, He and collaborators developed a nanoreactor based on oligo(ethylene glycol) monomethyl ether methacrylate (OEGMA) mixed with synthetically derived eosin Y (derived EoS) and ONB oxycarbonyl aminoethyl methacrylate (NBOC) hydrophobic monomer with an ONB photolabile group ( Figure 12 ) [ 303 ]. The resulting amphiphilic diblock copolymer P(OEGMA-co-EoS)-b-PNBOC (POPN) was synthesized via RAFT polymerization.…”
Section: Light-responsive Polymersomes For Anticancer Therapeutic Del...mentioning
confidence: 99%
“… Schematic illustration of ( a ) amphiphilic copolymer POPN, ( b ) polymersome self-assembly with a permeability conversion mechanism, and ( c ) mitochondrion location and the intracellular delivery of AQ4N and PDT activated by NIR. Reprinted with permission from [ 303 ]. Copyright © 2022, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…16 To increase their versatility in polymersome compositions, block copolymers have been combined with low molecular weight compounds or biomolecules 38 or substituted with amphiphilic homopolymers, polypeptides, glycoproteins, starch, polycarbonates, graft copolymers, 4,50 and bottlebrush polymers. 51 In addition to drug delivery, and because of the high stability and similarity in structure to cell membranes, polymersomes have also been investigated for biomedical applications including gene therapy, 52 magnetic resonance imaging (MRI), 53 artificial organelles, 54 protocellular constructs, 55 tumor therapy, 56 bacteria inhibition, 57 anti-inflammation, 58 active surfaces, 59 cancer theranostics, 5 and cell mimicking. 60 Their utility has also been expanded to fields such as compartments for nanoscale in situ reactions and nanoreactors, 61,62 nanodevices, 63 nanosensors, 64 catalysis, 65 and water treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The grafted EG chains drastically improve the water solubility and biocompatibility of methacrylate polymers, facilitating the broad adoption of POEGMA in the biomedical field . Similar to poly­(ethylene glycol) (PEG), POEGMA is often conjugated to various therapeutic agents, including peptides, proteins, , and nanoparticles, which can prevent immunogenicity and improve the circulation half-life of these therapeutic materials, leading to enhanced therapeutic efficacy. In particular, micelles composed of amphiphilic block polymers of hydrophilic POEGMA and hydrophobic polymers have been extensively investigated in the field of drug delivery aiming at tumor-targeted theranostics (therapy + diagnosis). Gao et al also reported the conjugation of POEGMA and proteins (green fluorescence protein; GFP) with improved stability and tumor uptake by CT26 tumors. , …”
Section: Introductionmentioning
confidence: 99%